A new direct synthesis of α-methylene- and α-alkylidene-β-lactams. Issue 18 (4th May 2016) - Hussein, Marwa; Nasr El Dine, Assaad; Farès, Farès; Dorcet, Vincent; Hachem, Ali; Grée, René
Graphical abstract: Highlights: New simple (1 step) method for the preparation of these challenging molecules. Method using cheap and easily available reagents. These methylene and alkylidene beta lactams have interesting potential in bioorganic and medicinal chemistry. Abstract: The Kinugasa reaction applied to alkynes bearing a nucleofuge in propargylic position affords directly, and in fair yields, α-methylene- or α-alkylidene-β-lactams.